Impact of household air pollution exposure on rural India: A systemic review - S. Singh; P. Dixit (Environment Conservation Journal, 2019)
All in developing nations about 50% population rely on solid unclean fuel in the form of animal dung cake, crop residue and wood for household energy and cooking. Solid biomass fuel is typically burnt in traditional cooking stove or chulha without chimney with incomplete combustion. As well as in rural areas children and women must go through the drudgery and health risk of collecting crop residue and fire wood. So the scheme of “Ujjwala Yojana” was commenced by the Prime Minister of India in 2016 and Rs. 8000 Cr. has been granted for the Yojana. The aim of this scheme was to provide safety for children and women in rural areas from health risk by furnishing with clean and safe cooking energy Liquid Petroleum Gas (LPG), so that they don’t have to deal their health issues in poor ventilated and smoky, blackish kitchen. Villagers were used traditional biomass stoves or chulha without chimney for cooking, boiling water and used for cooking cattle food. Aim of this review was to find out household air quality of rural areas using different solid unclean biomass fuel for example cow dung cake, crop remains and wood in terms of gaseous pollutants and particulate matter in kitchen area so the higher concentration of different gaseous pollutants i.e. carbon monoxide (CO), carbon dioxide (CO2), nitrogen dioxide (NO2) and sulphur dioxide (SO2) were reported in the kitchen area during cooking hours. It can be concluded based on literature reviews that, there is significant health risk associated with increased concentration of gaseous pollutants and suspended particulate matters.